ANALISA PEMELIHARAAN KOREKTIF PADA SYRINGE PUMP - Sitorus, Tenberry; Dabukke , Hotromasari; Situmorang, Harold; Priyulida, Fitria (JURNAL MUTIARA ELEKTROMEDIK, 2022)
Research has been carried out on the analysis of corrective maintenance on Syringe pumps. Maintenance of medical equipment is very important, which is useful for extending the service life of the equipment and ensuring the performance of the equipment to function according to its specifications. Corrective maintenance is a maintenance activity that is repairing damaged equipment with or without replacement of spare parts. This maintenance is intended to restore the damaged equipment to a usable and operational condition. The purpose of the study was to determine the of the Syringe Pump maintenance. The method used is Observational and Qualitative. The results of the research are Damaged Batteries, Soaks, Empty Alarm Sensors, Syringe Size sensors, Power Supply completely dead, the solution is after measurement and analysis. Syringe Pump found a Syringe size sensor problem that is not functioning properly, the solution is to replace the new Syringe size sensor. Syringe pump Supply is totally dead, the solution is to replace the 5 ampere fuse. Empty on the Syringe Pump is damaged, the solution is to replace the empty sensor. So the solution is to replace the battery with a new battery.